Early COPD Risk Decision for Adults Aged From 40 to 79 Years Based on Lung Radiomics Features - Yang, Yingjian; Li, Wei; Guo, Yingwei; Liu, Yang; Li, Qiang; Yang, Kai; Wang, Shicong; Zeng, Nanrong; Duan, Wenxin; Chen, Ziran; Chen, Huai; Li, Xian; et al. (Frontiers in Medicine, 2022)
Background： Chronic obstructive pulmonary disease (COPD) is a common and preventable lung disease. COPD has the highest prevalence in the elderly and deserves special consideration regarding treatment in this fragile population. Understanding the COPD risk of the aging process in the lungs is necessary to provide optimal care to adults. Methods: The 468 Chinese subjects aged 40 to 79 at the entire inspiration state undergo chest high-resolution computed tomography (HRCT) scans. The lung parenchyma images are segmented from the chest HRCT images by ResU-Net. The 1316 lung radiomics features are calculated from lung parenchyma images of each subject using PyRadiomics. The lung radiomics features are divided into four groups A-D according to the COPD stages, and the ages are divided into eight equal age intervals. The Lasso model is individually applied to select the lung radiomics features of the four groups. The four survival Cox models are constructed based on the selected lung radiomics features to predict the COPD risk probability. The four COPD risk ranks are defined by equally dividing the COPD risk probability from 0 to 1. Subsequently, the COPD risk at different stages is evaluated with varying age intervals. Results: The age intervals of each COPD risk rank of the patients who had suffered the COPD are the same. The risk rank levels up every five years for the subjects who had suffered from COPD after 60. For the subjects with COPD stage 0, the risk rank of suffering COPD stage I levels up every five years after the age of 65, and the risk rank of suffering COPD stage II and Ⅲ & Ⅳ levels up every five years after the age of 70. Conclusions: It concludes that once the age is over 60, the patients with COPD need to be paid close attention to prevent the progress and deterioration of COPD, and once the age is over 65, the patients with COPD stage 0 need to take precautions against COPD.